EFFECT OF AGARWOOD (Aquilaria malaccensis Lam) AROMATHERAPY ON ANXIETY AND PARENTING STRESS AMONG MOTHERS OF CHILDREN WITH SPECIAL NEEDS - I Kadek Surya Mahajayadi; I Gusti Agung Ayu Kartika; I Nyoman Yoga Segara; Ni Ketut Sinarsih (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2026)
Background: Parents of children with special needs often experience psychological distress, including anxiety and parenting stress, due to the continuous demands of caregiving and concerns regarding their children's development and future. Long-term psychological burden may adversely affect parental well-being and caregiving quality. Agarwood (Aquilaria malaccensis Lam) is a medicinal plant containing various bioactive compounds, including flavonoids, alkaloids, terpenoids, and essential oils, which have been reported to exhibit sedative, anxiolytic, and relaxation effects. Objective: This study aimed to determine the effect of agarwood aromatherapy on anxiety levels and parenting stress among mothers of children with special needs. Methods: A pre-experimental study with a one-group pretest-posttest design was conducted among mothers of children with special needs selected through purposive sampling. Anxiety levels were assessed using the State-Trait Anxiety Inventory (STAI), while parenting stress was measured using the Parenting Stress Index (PSI). Agarwood aromatherapy was administered through inhalation during the intervention period. Data were analyzed using descriptive and inferential statistical methods with a significance level of p < 0.05. Results: The results showed that agarwood aromatherapy did not significantly reduce anxiety levels measured by STAI (p > 0.05). Most participants remained in the moderate anxiety category throughout the intervention period. However, a significant reduction in parenting stress scores was observed after the intervention (p < 0.05). Conclusion: Agarwood aromatherapy was effective in reducing parenting stress but did not significantly affect anxiety levels among mothers of children with special needs. Therefore, agarwood aromatherapy may serve as a complementary intervention to improve parental psychological well-being. Keywords: Agarwood; Aromatherapy; Anxiety; Parenting stress; Special needs children